The Subarachnoid Hemorrhage Early Brain Edema Score Predicts Delayed Cerebral Ischemia and Clinical Outcomes. Issue 1 (7th July 2017) - Ahn, Sung-Ho; Savarraj, Jude P; Pervez, Mubashir; Jones, Wesley; Park, Jin; Jeon, Sang-Beom; Kwon, Sun U; Chang, Tiffany R; Lee, Kiwon; Kim, Dong H; Day, Arthur L; Choi, H Alex
Abstract: BACKGROUND: Early brain injury (EBI) after subarachnoid hemorrhage (SAH) is an important determinant of clinical outcomes. However, a major hindrance to studies of EBI is the lack of radiographic surrogate marker. OBJECTIVE: To propose a scoring system based on early changes in clinically obtained computed tomography (CT), called the Subarachnoid hemorrhage Early Brain Edema Score (SEBES). METHODS: Patients with spontaneous aneurysmal SAH and a CT within 24 h of ictus were included. We defined SEBES as a scale of 0 to 4 points according to the (1) absence of visible sulci caused by effacement of sulci or (2) absence of visible sulci with disruption of the gray–white matter junction at 2 predetermined levels in each hemisphere. Prognostic value of the SEBES grade for the prediction of delayed cerebral ischemia (DCI) and unfavorable outcomes was assessed. A separate cohort of patients was used as a validation cohort. RESULTS: Of the 164 subjects in our study, high-grade SEBES (3 or 4 points) was identified in 48 patients (29.3%). CT interobserver reliability of SEBES grades was high with a Kappa value of 0.89. After adjusting for covariables, SEBES was identified as an independent predictor of DCI (OR = 2.24, 95% CI: 1.58–3.17) and unfavorable outcome (OR = 3.45, 95% CI: 1.95–6.07). In our validation cohort, 84 subjects showed similar predictive power of SEBES for a prediction of DCI and unfavorable long-term outcome. CONCLUSION: SEBES may be a surrogate marker of EBI and predicts DCI and clinical outcomes after SAH.